2012
DOI: 10.1155/2012/875909
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of an ELISA Assay Using Excretion/Secretion Proteins from Epimastigote Forms ofT. cruzi(ESEA Antigens) for the Diagnosis of Chagas Disease

Abstract: An indirect enzyme-linked immunoabsorbent assay (ELISA) for Trypanosoma cruzi was developed using epimastigote secretion/excretion proteins (ESEA antigens) obtained from axenic culture supernatants. A panel of 120 serum samples from subjects with confirmed Chagas disease (n = 50), healthy controls (n = 50), and patients with other parasitic diseases (n = 20) was used to evaluate the new ESEA-based ELISA (ELISAESEA). This new test had excellent sensitivity (98%) and acceptable specificity (88%). Cross-reactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Despite the high sensitivity of different serological tests for the diagnosis of Chagas disease, the cross-reactivity mainly with sera from the VL and ACL patients is still frequent (Nakazawa et al, 2001;Amato Neto et al, 2005;Berrizbeitia et al, 2006Berrizbeitia et al, , 2012. Berrizbeitia et al (2012) demonstrated that despite the high sensitivity of this test for the diagnosis of Chagas disease, employing secreted/ excreted protein of epimastigotes, its specificity was only 88%, and cross-reactions were observed with Ascaris spp. and Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high sensitivity of different serological tests for the diagnosis of Chagas disease, the cross-reactivity mainly with sera from the VL and ACL patients is still frequent (Nakazawa et al, 2001;Amato Neto et al, 2005;Berrizbeitia et al, 2006Berrizbeitia et al, , 2012. Berrizbeitia et al (2012) demonstrated that despite the high sensitivity of this test for the diagnosis of Chagas disease, employing secreted/ excreted protein of epimastigotes, its specificity was only 88%, and cross-reactions were observed with Ascaris spp. and Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…The Camargo method was employed for IFA, using complete forms of T. cruzi epimastigotes isolated from strain Y (of Brazilian origin) and strain T3 (of Mexican origin, state of Veracruz, derived from in vitro cultures in Grace medium). Samples with titres > 1:16 were considered positive ( Camargo et al 1986 , Berrizbeitia et al 2012) .…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…The extracted enzyme was purified, fractioned and used as an antigen in Western blots to detect anti- T. cruzi antibodies in the 1,033 serum samples. The test was considered to be positive when anti- T. cruzi antibodies were detected at a dilution of 1:80 ( Marín & Sánchez-Moreno 2010 , Berrizbeitia et al 2012) . Evaluations of statistically significant differences between the tests were based on sensitivity, specificity, negative and positive predictive values, concordance percentage and the kappa index.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were referred to the JD MacLean Centre for Tropical Diseases at the McGill University Health Centre (Montreal, Quebec) for assessment. Blood was drawn for confirmatory serological testing using a T cruzi excreted-secreted antigen ELISA (TESA-ELISA) ( 14 , 15 ) and PCR by the National Reference Centre for Parasitology (NRCP) in Montreal. Some samples were also tested using RIPA by Quest Diagnostics (USA).…”
Section: Case Presentationmentioning
confidence: 99%